Dinamika Perkembangan Qawā‘id al-Tafsīr: Dari Konsep Dasar hingga Ruang Lingkup Penerapannya - M. Rayhan; Halimah Basri; Amir Hamzah (Dirosah Islamiyah, 2026)
Qawā‘id al-tafsīr holds an important position in Qur’anic studies because it serves as a methodological guideline for exegetes in understanding and explaining Qur’anic verses accurately. This study aims to analyze the definition, historical development, and scope of qawā‘id al-tafsīr. The research employed a library research method by collecting data from books, journal articles, and various classical and contemporary sources related to the principles of Qur’anic interpretation. The data were analyzed using a descriptive-analytical approach through the processes of description, examination, and interpretation of the relevant concepts. The findings indicate that qawā‘id al-tafsīr refers to a set of general rules or principles used as guidelines in interpreting Qur’anic verses in accordance with their intended meanings. Historically, the principles of qawā‘id al-tafsīr had been applied since the time of the Prophet Muhammad, who was the first interpreter of the Qur’an, and were subsequently continued by the Companions, the Successors, and later generations of scholars. Initially, these principles were not formulated as an independent discipline but were dispersed across works of Qur’anic exegesis, ‘ulūm al-Qur’ān, Islamic legal theory, and Arabic linguistics. Over time, qawā‘id al-tafsīr underwent a process of codification and developed more systematically from the classical to the contemporary period. Its scope includes linguistic principles and contextual principles related to the circumstances of revelation, particularly asbāb al-nuzūl. Therefore, mastery of qawā‘id al-tafsīr is essential for producing systematic and comprehensive interpretations and for avoiding errors in understanding the Qur’an.